Low-level jets and their implications on air pollution: A review - Wei, Wei; Zhang, Hongsheng; Zhang, Xiaoye; Che, Huizheng (Frontiers in Environmental Science, 2023)
Low-level jets (LLJ) are a common phenomenon in the atmospheric boundary layer and have been reported worldwide. Additionally, they have considerable relevance in a series of fields. This review aimed to document their implications on air quality, specifically particulate matter, mineral dust, and ozone in recent literature focus on i) generalizing long-range advection of pollutants by the low-level jets; ii) analysing vertical transport due to low-level jets-enhanced turbulence mixing and the corresponding mechanisms for different pollutants; and iii) introducing the performance of state-of-the-art numerical models. Finally, we suggest that high-resolution spatiotemporal observations of the pollutants and turbulence must be conducted, and current parameterization schemes should be improved to better represent the low-level jets and nocturnal boundary layer structures for reproducing the complicated interactions between the low-level jets and pollutants.